THE RELATIONSHIP BETWEEN NOISE INTENSITY AND WORKER CHARACTERISTICS WITH HEARING DISORDERS IN DENTAL LABORATORY JAKARTA - Wiyanti, Sri Wiwik; Prawesthi, Endang; Mujiwati, Mujiwati (Journal of Vocational Health Studies, 2021)
Background: Along with the development of processing goods using machine tools and equipment as well as the use of chemicals, one of the impacts is loud or noisy sound, which can be interpreted as unwanted sound or exceeding threshold and has an opportunity to damage hearing so that can be detrimental. Purpose: To analyze the relationship between the noise intensity and worker's characteristics with hearing disorders at the Dental Engineering Laboratory in the Jakarta area in 2020. Method: This research was an analytical study with a descriptive cross-sectional design with a sample of 30 dental technicians who work in a dental engineering laboratory in the Jakarta area. Each area is taken 6 people. Measurement of noise in the laboratory with a sound level meter and measurement of hearing loss with audiometry. Result: Workers whose noise intensity is >85 dBA have hearing loss, workers whose noise intensity is 85 dBA, 4 people who have hearing loss, workers aged >40 years have hearing loss, while among workers aged â‰¤40 years, there are 7 people experiencing hearing disorders. workers with >5 years of service experience hearing loss, while among workers 5 years of service, none have hearing loss. Conclusion: There is a significant between noise intensity with hearing loss (p-value = 0.011), it isn't significant between age with hearing loss (p-value = 0.0563), and it isn't significant between tenure with hearing loss (p-value = 0.06).